THE Effects of Motivational Interviewing on Motion Sickness - Unal DEMIRTAS; Mehmet Ergin DIPCIN; Mehmet CETIN (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
We did a duty as a flight surgeon. We want to share our experiences about motion sickness and the effects of motivational interviewing on motion sickness. [JCBPR 2015; 4(3.000): 184-185]